Kriz ve korumacılık: Tarih tekerrür edecek mi? - Sumru Öz (TÜSİAD-Koç University Economic Research Forum, 2009)
As a result of the current global financial crisis, in 2009 the world economy is likely to experience the largest contraction since World War II and the unemployment rate to reach historical highs in many countries. The fact that the current global crisis is originated from the U.S. and followed another intensive wave of globalization, has led to an unprecedented public interest towards the Great Depression of 1929-1933. These parallels between the two episodes further fueled the fears that the current crisis would deepen and last a couple of years, similar to the Great Depression. The aim of this paper is to discuss the validity of these worries by studying the root causes of the current crisis in the light of the causes of the Great Depression as laid out by the related literature. The paper concludes that the factors that deepen and widen the Great Depression are not valid anymore to a great extent. Together with the decisions taken by the leaders of the world's largest economies at the London Summit in April, the conclusions of the paper keep the hope that the current global crisis will not turn into a severe global depression.
Keywords: N72; F13; E32; 330; Great Depression; Global Criisis; International Trade; Protectionism; Weltkonjunktur; Wirtschaftskrise; Internationale Wirtschaftsbeziehungen; Protektionismus; Welt